Kontrola srdeční frekvence versus kontrola rytmu u nemocných se srdečním selháním - Roy, Denis (Clinical Cardiology Alert, 2008)
It is common practice to restore and maintain sinus rhythm in patients with atrial fibrillation and heart failure. This approach is based in part on data indicating that atrial fibrillation is a predictor of death in patients with heart failure and suggesting that the suppression of atrial fibrillation may favorably affect the outcome. However, the benefits and risks of this approach have not been adequately studied. METHODS: We conducted a multicenter, randomized trial comparing the maintenance of sinus rhythm (rhythm control) with control of the ventricular rate (rate control) in patients with a left ventricular ejection fraction of 35% or less, symptoms of congestive heart failure, and a history of atrial fibrillation. The primary outcome was the time to death from cardiovascular causes. RESULTS: A total of 1376 patients were enrolled (682 in the rhythm-control group and 694 in the rate-control group) and were followed for a mean of 37 months. Of these patients, 182 (27%) in the rhythm-control group died from cardiovascular causes, as compared with 175 (25%) in the rate-control group (hazard ratio in the rhythm-control group, 1.06; 95% confidence interval, 0.86 to 1.30; P=0.59 by the log-rank test). Secondary outcomes were similar in the two groups, including death from any cause (32% in the rhythm-control group and 33% in the rate-control group), stroke (3% and 4%, respectively), worsening heart failure (28% and 31%), and the composite of death from cardiovascular causes, stroke, or worsening heart failure (43% and 46%). There were also no significant differences favoring either strategy in any predefined subgroup. CONCLUSIONS: In patients with atrial fibrillation and congestive heart failure, a routine strategy of rhythm control does not reduce the rate of death from cardiovascular causes, as compared with a rate-control strategy. (ClinicalTrials.gov number, NCT00597077.) 2008 Massachusetts Medical Society
Keywords: dysfunkce levé srdeční komory; Humans; Digitalis Glycosides; lidé; prospektivní studie; amiodaron; Hospitalization; Angiotensin-Converting Enzyme Inhibitors; kardiovaskulární nemoci; hospitalizace; Prospective Studies; Adrenergic beta-Antagonists; elektrická defibrilace; Combined Modality Therapy; Female; lidé středního věku; kombinovaná terapie; Electric Countershock; antiarytmika; Amiodarone; Male; Kaplan-Meier Estimate; následné studie; Follow-Up Studies; Heart Failure; Heart Rate; Atrial Fibrillation; Cardiovascular Diseases; srdeční frekvence; beta blokátory; senioři; srdeční selhání; digitalisové glykosidy; Aged; fibrilace síní; Middle Aged; ženské pohlaví; mužské pohlaví; inhibitory ACE; Kaplanův-Meierův odhad; Ventricular Dysfunction, Left; Anti-Arrhythmia Agents